DRAFT «ASPINE» MOBILE APPLICATION FOR PATIENTS WITH EARLY AXIAL SPONDYLOARTHRITIS - D. G. Rumiantceva; T. V. Dubinina; Sh. F. Erdes (Научно-практическая ревматология, 2018)
Telemedicine, including mobile applications for patients, is progressing rapidly now. However, patients with axial spondyloarthritis (axSpA) still have no applications that can be used to monitor their health status independently and to contact their physician remotely. Objective: to develop and test an «ASpine» mobile application for smartphones in real clinical practice. Material and methods. The draft «ASpine» mobile application has two parts: a mobile application for patient and a personal computer program used by a rheumatologist to monitor disease activity in patients. The patient part of «ASpine» consists in filling out the BASDAI and BASFI questionnaires and monitoring how recommendations for daily exercise therapy and medications are fulfilled. There is also an opportunity for constant contact with the physician through the mobile application. The patients from the Moscow cohort CoESAr (Cohort of Early SpondyloArthritis) which was made up at the V.A. Nasonova Research Institute of Rheumatology in 2013 and is being formed to the present time took part in mobile application testing. Results and discussion. The mean scores of BASDAI at inclusion and after 12-month follow-up were 3.3±1.7 and 2.1±1.7 (p > 0.5) and those of BASFI were 1.6±1.3 and 1.3±1.2, respectively (p > 0.5). To analyze the health status of 35 patients, one doctor requires 1 min daily if there are no reports of their worse health. It takes an average of 5–8 min to make a decision if the patient reports the occurrence of any symptom or an adverse reaction. The findings can lead to the conclusion that the «ASpine» mobile application allows patients to independently monitor disease activity, to store medical records, and to contact their physician remotely. Continuous monitoring of the patient's condition makes it possible to maintain low disease activity or remission for a long time.